Composición cualitativa y cuantitativa del fitoplancton marino nerítico superficial (dinophyceae y bacillariophyceae) de puerto malabrigo - peru, noviembre 2006 – noviembre 2007 - Alvítez Izquierdo, Elmer (2008)
Present announces qualitative and quantitative composition of marine phytoplankton superficial neritico (Dinophyceae and Bacillariophyceae) of port Malabrigo - Peru, November, 2006 - November, 2007, on two fixed stations of sampling, Station N º 1: 7°41 ' 35,3 " S - 79°26 ' 34,2 " Or and Station N º 2: 7°43 ' 24,6 " S - 79°31 ' 18,6 " O), by means the analysis of 46 samples obtained every two weeks. The analysis of samples allowed to determine 78 species(kinds), of them 52 are Bacillariophyceae and 26 Dinophyceae. The parameters físicoquímicos of marked fluctuation were temperature and transparency of water, as well as oxygen disuelto. The average values of diversity they were similar for both stations, and they are 2.52785868 and 2.46277302. The Index of Sorensen's Similarity was 93 %. There are demonstrated warning species of environmental, such as: Ceratium tripos, C. falcatum, C. breve, C. macroceros and Protoperidinium obtusum. Likewise four new nomenclaturales combinations are adopted of the genres, Proboscia, Calyptrella, Asteriollenopsis and Pseudonitzschia. The genres with more diversity of species were: Protoperidinium (12 species), Chaetoceros (7), Ceratium (6), Coscinodiscus (6), Thalassiosira (5) and Dinophysis (4).